2006
DOI: 10.1056/nejmoa061752
|View full text |Cite
|
Sign up to set email alerts
|

Endarterectomy versus Stenting in Patients with Symptomatic Severe Carotid Stenosis

Abstract: In this study of patients with symptomatic carotid stenosis of 60% or more, the rates of death and stroke at 1 and 6 months were lower with endarterectomy than with stenting. (ClinicalTrials.gov number, NCT00190398 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
626
2
27

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,414 publications
(672 citation statements)
references
References 22 publications
17
626
2
27
Order By: Relevance
“…From what has been described, it appears clear that the biggest limitations of the study are the scarce endovascular technique experience of the operators (12 carotid artery stentings or 35 procedures performed on supra-aortic trunks, of which five were carotid) and the preprocedural anti-platelet therapy which was only recommended and not always homogeneously administered. Double anti-platelet therapy was administered to 82.9% of the patients and only 85.4% were administered anti-platelet therapy after the intervention [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From what has been described, it appears clear that the biggest limitations of the study are the scarce endovascular technique experience of the operators (12 carotid artery stentings or 35 procedures performed on supra-aortic trunks, of which five were carotid) and the preprocedural anti-platelet therapy which was only recommended and not always homogeneously administered. Double anti-platelet therapy was administered to 82.9% of the patients and only 85.4% were administered anti-platelet therapy after the intervention [16].…”
Section: Discussionmentioning
confidence: 99%
“…While in the CAVATAS and SAPPHIRE studies the periprocedural complication rate (stroke and death) of CEA and CAS are comparable with a greater risk/benefit ratio in patients at high risk for surgery; EVA-3S reported a higher complication rate in CAS [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few data exist on the utilization of statin therapy among patients with carotid artery disease. In the multicenter randomized controlled EVA‐3S (Endarterectomy Versus Angioplasty in Patients with Symptomatic Severe Carotid Stenosis) and SPACE (Stent‐Supported Percutaneous Angioplasty of the Carotid Artery Versus Endarterectomy) trials, only 49% of patients were on lipid‐lowering therapy at the time of carotid revascularization 10, 11. This is particularly concerning, given data from the SPARCL (Stroke Prevention by Aggressive Reduction in Cholesterol Levels) trial that showed carotid stenosis patients derive the greatest benefit from intense statin therapy with respect to adverse cerebro‐ and cardiovascular events 12…”
Section: Introductionmentioning
confidence: 99%
“…CREST (Carotid Revascularization Endarterectomy versus Stenting Trial)10 reported the shortest median interval; this was still 22 days for CEA and 18 days for CAS. In all except two RCTs, the mean delay from the index event to revascularization was greater than 1 month9, 12, 14. Even in studies that mostly revascularized sooner after the index event, the mean delay was above the 2‐week threshold3, 10.…”
mentioning
confidence: 88%
“…Of the 12 RCTs3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 that have compared carotid endarterectomy (CEA) with carotid artery stenting (CAS) in patients with significant carotid stenosis, only five3, 9, 10, 12, 14 provided information on the time from the index event to revascularization. CREST (Carotid Revascularization Endarterectomy versus Stenting Trial)10 reported the shortest median interval; this was still 22 days for CEA and 18 days for CAS.…”
mentioning
confidence: 99%